Ionizing radiation exposure in humans during X-ray procedures in dogs and cats: A systematic review - Arcila-Giraldo, Adrián C; Correa-Valencia, Nathalia M (Revista Colombiana de Ciencias Pecuarias, 2025)
Background: Ionizing radiation in veterinary medicine enhances diagnosis and treatment but poses risks to animals, pet owners, and clinical staff. Inadequate training in radiographic equipment use increases the risk of unnecessary exposure and related hazards. Objective: To systematically gather and analyze the available evidence on ionizing radiation exposure in human individuals involved in X-ray diagnostic procedures performed in dogs and cats. Methods: An electronic search on four platforms, followed by a manual review of references from articles identified in full-text screening, was conducted. References from six selected review articles (1997-2022) were also examined. Predetermined inclusion and exclusion criteria were strictly applied, focusing solely on articles published in peer-reviewed journals. Results: A total of 5 articles met the definitive inclusion criteria. The relevant articles were published between 2007 and 2024. The levels were low (about 90% of the measurements showed doses below 0.005 mSv), with exposure peaks observed in critical anatomical areas such as the veterinary staff´s eyes and hands, particularly during procedures requiring proximity to the radiation field. Conclusion: Our results highlight the need to increase awareness of the need for proper training and the implementation of radiological protection measures to minimize the risks associated with ionizing radiation in veterinary practices. In addition, future research needs to incorporate a wider range of devices and techniques to develop safety protocols that safeguard staff and patients.